Coupling of Ribostasis and Proteostasis: Hsp70 Proteins in mRNA Metabolism - Walters, Robert W (Trends Biochem Sci, 2015)
A key aspect of the control of gene expression is the differential rates of mRNA translation and degradation, including alterations due to extracellular inputs. Surprisingly, multiple examples now argue that Hsp70 protein chaperones and their associated Hsp40 partners modulate both mRNA degradation and translation. Hsp70 proteins affect mRNA metabolism by a variety of mechanisms including regulating nascent polypeptide chain folding, activating signal transduction pathways, promoting clearance of stress granules, and controlling mRNA degradation in an mRNA-specific manner. Taken together, these observations highlight the general principle that mRNA metabolism is coupled to the proteostatic state of the cell, often as assessed by the presence of unfolded or misfolded proteins.